The Effect of Some Organic Compounds on Monoamino oxidase Activity - Muftin, Najlaa Qasim (Al-Nahrain Journal of Science, 2018)
Imidazole derivatives have occupied a unique place in the field of medicinal chemistry. The incorporation of the imidazole nucleus is an important synthetic strategy in drug discovery. The high therapeutic properties of the imidazole related drugs have encouraged the medicinal chemists to synthesize a large number of novel chemotherapeutic agents. This study was designed to show the effects of new compounds derivatives from 2-Imidazolidine thione on the activity of Monoamino oxidase in sera. All compounds were studied demonstrated inhibitory effects on the enzyme activity and these effects are increased with increasing the concentrations of the compounds. The compound 2-(4,5-dihydro-1H-imidazol-2-ylthio)-N’-(2-hydroxy benzylidene) acetohydrazide has the highest ability to inhibit MAO than the other compounds.Kinatic properties of these inhibitors reveal that compound 4 causes mixed type of inhibtion,componds 1,3 act as non -competitive inhibitor and compound 2 behaves as un- competitive inhibitor.